Urbanization and poverty in Sub-Saharan Africa: evidence from dynamic panel data analysis of selected urbanizing countries - Solomon Ahimah-Agyakwah; Edward Nketiah-Amponsah; Frank Agyire-Tettey (Cogent Economics & Finance, 2022)
Urbanization in Sub-Saharan Africa (SSA) is generally highlighted as a puzzle that deviates from the stylized facts in the literature. Using data from a panel of 29 urbanizing countries in SSA from 1985 to 2019, the study employs the two-step system generalized methods of moments to investigate the effect of urbanization on the Poverty Headcount ratio and Poverty Gap. The estimated urbanization elasticities of poverty indicate that at growth rates, a 1 percentage point increase in urbanization rate induces 0.04 and 0.05 (0.07 and 0.09) percentage points decrease in the Poverty Headcount ratio and Poverty Gap in the short-run (long-run), respectively. Similarly, at levels, a 1 percent increase in urbanization level induces 0.22 and 0.32 (0.60 and 0.68) percent decrease in the Poverty Headcount ratio and Poverty Gap in the short-run (long-run), respectively. Consistently, these results show stronger effect of urbanization on the depth of poverty relative to the incidence of poverty. These findings reappraise the literature on the urbanization of poverty in SSA as well as provide a nuanced understanding of the effect of urbanization on the different class of poverty measures. Notwithstanding, the poverty reduction potential of urbanization is not automatic and requires enormous investment in public infrastructure to achieve.
Keywords: 330; urbanization; poverty; elasticities; generalized methods of moments; SubSaharan Africa